Performance of Mangalore Melon Selections in Farmer’s Field - Shet, Ratnakar M.; Hongal, Shivanand; Gunnaiah, Raghavendra (International Journal of Economic Plants, 2021)
Mangalore melon (Cucumis melo var. acidulus) is a kind of non-dessert culinary melon belongs to family Cucurbitaceace. It is widely cultivated in Southern parts of Indian subcontinent. It is mainly utilized for culinary purpose especially preparation of lentil soup, sambar, dosa, palya and chutney. It is locally referred as Mangalore Southe, Sambar southe, Mogem etc. A total of 80 accessions were collected from six southern Indian states namely, Karnataka, Kerala, Andhra Pradesh, Tamil Nadu, Telangana and Goa. The germplasm accessions were evaluated and characterized for quantitative and qualitative traits during Kharif 2018 and Summer season of 2019 at College of Horticulture farm, Sirsi, Karnataka. The top performing 14 selected accessions of South Indian Mangalore melon during two season evaluation were subjected for their yield performance assessment under progressive farmer’s field during summer season 2020 in Uttara Kannada district of Karnataka. All the selected accessions performed better compare to station trail. The accessions namely MS-28, MS-30, MS- 74, MS-78 and MS-79 found to be superior for yield performance. Generally, fruits of Mangalore melons are variable in size, shape, color and shelf life. However, local consumers preferred fruits with green color, high shelf life and the fruit color which does not change on maturity. Present study helps to know the local required Mangalore melon type for consumers as well as for farmer’s income generation.